Utilizing One-Way Valve to Optimize Turbocharger Performance on a Blended EGR Engine - Handa, Gaurav; Denton, Bradley; Rengarajan, Sankar; Chadwell, Christopher; Conway, Graham (Frontiers in Mechanical Engineering, 2021)
Internal combustion engines (ICE) will be a part of personal transportation for the foreseeable future. One recent trend for engines has been downsizing which enables the engine to run more favorably over regulatory drive cycles. Another shift due to downsizing is the increase in engine power density which leads to problems with engine knock. One way to reduce the knock propensity of engines is by introducing Exhaust Gas Recirculation (EGR) into the combustion chamber. EGR also helps improve fuel economy and can reduce NOX emissions. EGR reduces volumetric efficiency which places challenges on the boosting system. LP-EGR helps to lower backpressure and improves scavenging which helps reduce knock and operate at a high efficiency at the low-speed and high-load conditions. At high-speed, and high-load operation however, LP-EGR operation can choke the compressor. This would mean that the turbocharger would need resizing to allow a higher mass flow at these higher speed-load conditions. The HP-EGR helps by reducing the flow rates to the compressor at the higher speed-load conditions which avoids compressor choke and permits a full load performance while retaining a smaller, more transient capable turbocharger. The concept of a one-way valve in the HP-EGR Loop has been explored in this paper. During HP-EGR operation, pressure pulsations drive the intake air back through the HP-EGR Loop and limit the maximum amount of HP-EGR. A one-way valve would prevent any backflow and permit a greater HP-EGR flow for a given average delta pressure. For a given EGR rate, this enables a wider throttle position and thus better controllability at the higher speed-load conditions. Engine testing with the one-way valve suggested that the HP-EGR rate at the high speed/load condition was nearly doubled while reducing the PMEP with an improvement in the Brake Specific Fuel Consumption (BSFC). Additionally, this led to more reasonable actuator positions in terms of the EGR valve and the intake throttle to ensure better controllability.